The Influence of Service Quality and Satisfaction on Costumer Loyalty at PT. Meida Wisata Tour and Travel - Ansar HK; Buyung Romadhoni; Syahrtini Indrayani (CV. AFDIFAL MAJU BERKAH, 2025)
This study is a quantitative descriptive research aimed at identifying and analyzing the influence of service quality and satisfaction on customer loyalty at PT. Meida Wisata Tour and Travel. The research methods used include observation, questionnaires, and documentation. The population and sample in this study consisted of 185 respondents, and the data analysis method employed is multiple linear regression, processed using the Statistical Product and Service Solutions (SPSS) Version 27 software.Based on the results of the research conducted, the t-test for variable (X1), which is service quality, on variable (Y), customer loyalty, showed that the calculated t-value is greater than the table t-value (11.947 > 0.143) and the significance value obtained is 0.000, which is smaller than the alpha value of 0.05 (0.000 < 0.05). From these values, it can be concluded that variable (X1) has a positive and significant influence on variable (Y) at PT. Meida Wisata Tour and Travel. Additionally, the t-test result for variable (X2), which is satisfaction, on variable (Y), customer loyalty, showed that the calculated t-value is greater than the table t-value (2.022 > 0.143) and the significance value obtained is 0.045, which is smaller than the alpha value (0.045 < 0.05). From these values, it can be concluded that variable (X2) has a positive and significant influence on variable (Y) at PT. Meida Wisata Tour and Travel.